Проблематика правової природи рекомендаційних роз’яснень Антимонопольного комітету України - Хамходера, Олег Петрович; Хамходера, О. П.; Хамходера, Олег Петрович; Khamkhodera, Oleh P.; Подцерковний, Олег Петрович; Подцерковний, О. П.; Podtserkovnyi, Oleh P.; Зятіна, Діна Володимирівна; Зятіна, Д. В.; Ziatina, Dina V. (My University, 2021)
Проведено науковий аналіз правової природи рекомендаційних роз’яснень Антимонопольного комітету України. Приділено детальну увагу вивченню положень Рекомендаційного роз’яснення Антимонопольного комітету України від 09.08.2016 № 39-рр, що визначає підходи Антимонопольного комітету України, які рекомендується використовувати його органам у процесі визначення штрафів за порушення законодавства про захист економічної конкуренції, зокрема порушень законодавства про захист від недобросовісної конкуренції, з метою забезпечення правової визначеності та передбачуваності застосування положень законодавства. На основі наукового дослідження зроблено висновок, що рекомендаційні роз’яснення Анти монопольного комітету України за своєю природою є актами загальної регулятивної дії, що не є нормативно-правовими актами, не можуть створювати нові норми права, належать до так званого м’якого права, за допомогою якого забезпечується однаковість інтерпретації та одноманітний порядок реалізації положень законодавства.

The article is devoted to the scientific analysis of legal nature of recommendation clarifications of Antimonopoly Committee of Ukraine. The detailed attention is paid to the thorough investigation of provisions of Recommended Clarifications of Antimonopoly Committee of Ukraine No. 39-pp August 08th, 2016 that defines the legal approaches of Anti monopoly Committee, which are recommended to apply by its official bodies while defining of fines for violation of legislation on protection of economic competition, including protection from unfair competition, in order to ensure the legal certainty and predictability of application of legal provisions. On the basis of scientific research, the conclusion is made that recommended clarifications of Antimonopoly Committee of Ukraine by their legal nature are the acts of common regulative force that are not the legislative acts, they also cannot create new legal provisions, they belong to the so called “soft law” by means of which the uniformity of interpretation and uniform rules for realization of legal pro visions are ensured. The importance of recommendation as interpretation of legal provisions is highlighted, their place in the regulation of legal relations is defined. The main purpose of recommendations is to form the legal opinion of state autho rity abot the content and the order of execution of legal provisions. The authors make a conclusion that withdrawal of Antimonopoly Committee of Ukraine from its own legal position as to the practice of fine calculation, that is prescribed in recommended clarifications, provides the possibility to talk about the violation of one of the major prin ciple of law — the principle of legal certainty. The proper realization of discretional competence is based on the compliance with the requirements of legality and adequacy of law enforcement decisions of empowered officials. With the purpose of improvement of current legislation, it is proposed to approve the Methodology for calculating the amount of fines by the Antimonopoly Committee of Ukraine for violation of the legislation on protection of economic competition. The adoption of such Methodological guidance for calculation of fines will increase the efficiency of national regulative provisions and goes completely in line with the provisions of Association Agreement between the European Union and Ukraine.
Подцерковний О. П. Проблематика правової природи рекомендаційних роз’яснень Антимонопольного комітету України / О. П. Подцерковний, Д. В. Зятіна, О. П. Хамходера // Економіка та право. – 2021. – № 2. – С. 3-15.
Keywords: рекомендаційні роз’яснення; Антимонопольний комітет України; проблеми правозастосування; м’яке право; recommended clarifications; Antimonopoly Committee of Ukraine; problems of application of law; soft law; Research Subject Categories::LAW/JURISPRUDENCE